B chromosome retrotransposed sequences persist through speciation, contributing to genomic and regulatory innovations in the fish genus Psalidodon (Characiformes, Acestrorhamphidae) - Lucas F. Lasmar; Mateus R. Vidal; Pamela C. F. Nadai; Rodrigo Zeni dos Santos; Raquel da Costa Machado; Ricardo Utsunomia; Francisco J. Ruiz-Ruano; Alexander Suh; Claudio Oliveira; Duilio M. Z. A. Silva; Fausto Foresti (PLoS ONE, 2026)
B chromosomes are supernumerary genetic elements rich in repetitive DNA. Many species within the fish genus Psalidodon possess a large metacentric B chromosome that exhibits signs of recent retrotransposon activity, resulting in truncated pseudogenic copies of standard A chromosomes genes, specifically sbno2 and simc1 . We aimed to characterize the structure of the B chromosome pseudogenes sbno2-B and simc1-B and their evolutionary history in four B chromosome variants of three Psalidodon species, as well as their expression patterns in Psalidodon paranae individuals with a single B chromosome (1B). Our findings suggest that the retrotransposition process of each gene occurred in an ancestral B chromosome, which later diverged into distinct trajectories within each species following speciation. In the high-copy B chromosomes, the sbno2-B pseudogene shows dozens of interspersed copies, while the simc1-B pseudogene usually shows three copies arranged in tandem. In Psalidodon paranae 1B individuals, underexpression of the sbno2 and simc1 genes in ovaries indicates that the pseudogenic B copies probably influence gene expression through non-coding RNA interference mechanisms. This shows that the retrotransposon activity on B chromosomes generates genomic diversity and neofunctionalization, impacting gene regulatory networks, and possibly contributing to the persistence of B chromosome in populations.